Substitution Method
Step 1: Solve for either x or y in 1 of the 2 equations.
x + y = -2
- x - x
------------------------
y = -x - 2
Step 2: Plug in the expression you got for x or y into the opposite equation.
-x - 2 = 4x + 4
+ 2 + 2
-------------------------------
-x = 4x + 6
-4x - 4x
------------------------
-5x = 6
---- -----
-5 -5
x = -6/5
Step 3: Plug in the value for x or y into the equation you didn't use in Step 2.
-6/5 + y = -2
+ 6/5 + 6/5
--------------------------
y = -4/5
(x,y) = coordinate pair
(-6/5, -4/5) = final answer